A Theoretical Review of the Formation of Religious Character in Early Childhood through the Method of Storytelling about the Prophets - Sri Widianti; Mufassirul Alam (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
The formation of religious character is crucial to protect children from moral degradation from an early age. This study aims to analyze the theoretical relevance of the method of storytelling about prophets to the development of children's character. Using a descriptive qualitative method of literature study, this study analyzed 20 primary literature sources consisting of accredited journals, tafsir books, and developmental psychology books. Data analysis used content analysis with four stages of reduction to synthesis. The results showed a 100% level of theoretical relevance between the storytelling method and children's psychological needs, which included four main dimensions: cognitive, affective, social, and spiritual. The data showed that the integration of moral messages through prophetic stories was consistently able to touch on all aspects of development in an integrated manner. It was concluded that the method of storytelling prophetic stories had a very strong pedagogical foundation and was effective as an instrument for internalizing religious character values in early childhood.